Monsoon failure trend and its implication for agriculture in the states of Punjab and Haryana - Gautam, R. C. (Indian Farming, 2016)
The world could suffer a 40% shortfall in water in just 15 yearsunless countries dramatically change their use of the resource, a UN report has warned. In many countries including India, water use is largely unregulated and often wasteful. Pollution of water is often ignored and unpunished. Climate change is expected to make the situation worse, as higher temperature and more erratic weather patterns could disrupt rainfall.